Sex differences in pre-incarceration mental illness, substance use, injury and sexually transmitted infections and health service utilization: a longitudinal linkage study of people serving federal sentences in Ontario - Tenzin Butsang; Arthur McLuhan; Leslie A. Keown; Kinwah Fung; Flora I. Matheson (BMC, 2023)
Abstract Background People who experience incarceration have poorer health than the general population. Yet, we know little about the health and health service utilization of people during the critical period prior to their incarceration, relative to during incarceration and post-release. In this study, we conducted a longitudinal cohort study of 39,498 adults in Ontario, Canada between January 1, 2002, and December 31, 2011 using linked administrative health and correctional data to describe mental illness, substance use, injury, sexually transmitted infections and health service utilization of men and women in federal prisons in the 3 years prior to their incarceration, compared to a matched group. Results We found that, in the 3-year period prior to their incarceration, men (n = 6,134) and women (n = 449) experiencing their first federal sentence had poorer health across all indicators examined (e.g., psychosis, drug/alcohol use, and self-harm) and higher outpatient psychiatric and emergency department visits, compared with the matched group. Women in the pre-incarceration group exhibited a higher prevalence of self-harm and substance use, relative to women in the matched comparison group and higher relative prevalence to that of men in the pre-incarceration group, compared to their matched counterparts. Conclusions Disparities in health and health service utilization are gendered and exist prior to incarceration. The gendered nature of these findings, specifically the significantly higher prevalence of poor health among women across several indicators, necessitates a focus on the social and systemic factors that contribute to these disparities. Gender-responsive and trauma-informed primary, secondary, and tertiary prevention strategies, alongside transformative approaches to justice should be considered in addressing the health needs of men and women who experience incarceration.